2023
DOI: 10.1038/s41467-023-38694-0
|View full text |Cite
|
Sign up to set email alerts
|

Detailed mapping of Bifidobacterium strain transmission from mother to infant via a dual culture-based and metagenomic approach

Abstract: A significant proportion of the infant gut microbiome is considered to be acquired from the mother during and after birth. Thus begins a lifelong and dynamic relationship with microbes that has an enduring impact on host health. Based on a cohort of 135 mother-infant (F = 72, M = 63) dyads (MicrobeMom: ISRCTN53023014), we investigated the phenomenon of microbial strain transfer, with a particular emphasis on the use of a combined metagenomic-culture-based approach to determine the frequency of strain transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Our analysis showed that strain transmission from mother to infant is rare in CS infants. CS delivery disrupts the mother-to-infant transmission of microbiota, as demonstrated by previous studies ( Korpela et al, 2018 ; Shao et al, 2019 ; Mitchell et al, 2020 ; Feehily et al, 2023 ). Korpela et al (2018) analyzed 25 infants and six 2- to 10-yr-olds born via CS.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our analysis showed that strain transmission from mother to infant is rare in CS infants. CS delivery disrupts the mother-to-infant transmission of microbiota, as demonstrated by previous studies ( Korpela et al, 2018 ; Shao et al, 2019 ; Mitchell et al, 2020 ; Feehily et al, 2023 ). Korpela et al (2018) analyzed 25 infants and six 2- to 10-yr-olds born via CS.…”
Section: Discussionsupporting
confidence: 62%
“…Performing strain transmission analysis from 178 mother-baby dyads, Shao et al (2019) found that maternal strain transmission occurred mainly in VD infants (74.39%) during the neonatal period, with a high rate of transmission compared to those delivered by C-section (12.56%). Feehily et al (2023) found that the diversity of species shared through vaginal births was greater than those transferred during CS, with only 7 different shared species observed with CS compared to 26 with vaginal births.…”
Section: Discussionmentioning
confidence: 89%
“…Despite K. pneumoniae potential association with silent sepsis in infants 49,50 and with mastitis and milk loss in cows 51 , the infants in our cohort showed no clinical manifestations nor had any of the mothers reported mastitis/breast inflammation at the time of their study visit and milk collection. While strain sharing between the maternal and the infant gut has been extensively investigated 8,11 , only one metagenomic study has so far, to the best of our knowledge, successfully identified strains shared between the maternal breast milk and the infant gut microbiome 52 . Our results provide evidence that strain sharing between the infant gut and the maternal breast milk occurs, even if at a rate considerably lower than what was previously found between the infant and the maternal gut 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The microbes in breast milk are considered to be the “fingerprints” from the mother. Research studies had found that the microbial communities in breast milk, especially Bifidobacterium , Streptococcus , and Lactobacillus , can colonize the infant gut through breastfeeding and help defend against pathogenic invasion, promote gut immune maturation, and prevent inflammation in early life (Feehily et al., 2023; Qi et al., 2022; Wang et al., 2023). Furthermore, compared with probiotics from other sources, human‐origin probiotics derived from breast milk are more likely to adapt to the human body environment and are easier to apply in production due to their inherent adaptation to dairy‐based matrices (Shokryazdan et al., 2017).…”
Section: Discussionmentioning
confidence: 99%